Biodiesel Making from Waste Vegetable Oils: A Case Study of Lab to Plant Technology Transfer - Shah, N G; Khan, Shoyeb; Mahajan, S M (Journal of Agricultural Engineering, 2010)
Great deals of efforts are being made to promote bio-diesel as an environment-friendly alternative to the petrodiesel to meet the increasing demands. Two important issues which are hindering the dissemination of the technology are: raw material availability at an affordable cost, and the acceptable quality of the bio-diesel satisfying the BIS standards. The study was undertaken with the duel objectives to make bio-diesel from cheaper unconventional raw materials, as well as to demonstrate a process at a pilot plant scale at users’ site. Wastes of vegetable oil refining such as acid oil as well as waste cooking oils were processed for making biodiesel. Process reported here used esterification, followed by transesterification of oil using methanol, and a chosen catalyst. The processes were initially studied on laboratory scale conversion units (20 l/batch), which enabled to determine the process parameters for the pilot field-unit (400 l/batch). The process flow design, mass balance, process time for the batch processes were established and are reported along with the important fuel properties of biodiesel such as density, viscosity, moisture content and flash point. The technology has been demonstrated for its technical performance at a Village Industry Centre, where the bio-diesel produced is used in-situ for electricity generation.